85.7k views
2 votes
Use basic trigonometric identities to simplify the expression: 2 sin (x) cos (x) sec (x) csc (x) = ?

User Tyler Muth
by
5.1k points

1 Answer

2 votes

Answer:


2sin(x)*cos(x)*sec(x)*csc (x)=2

Explanation:

Remember the identities:


sec(x)=(1)/(cos(x))\\\\csc(x)=(1)/(sin(x))

Ginven the expression:


2sin(x)*cos(x)*sec(x)*csc (x)

You need to substitute
sec(x)=(1)/(cos(x)) and
csc(x)=(1)/(sin(x)) into it:


2sin(x)*cos(x)*sec(x)*csc (x)=2sin(x)*cos(x)*(1)/(cos(x))*(1)/(sin(x))

Now, you need to simplify.

Remember that:


(a)/(b)*(c)/(d)=(a*c)/(b*d)

And:


(a)/(a)=1

Then, you get:


=(2sin(x)*cos(x))/(cos(x)*sin(x))}=2

User Felix Lamouroux
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.